Polynomial-Based Robust Adaptive Impedance Control of Electrically Driven Robots. Issue 7 (4th July 2021) - Izadbakhsh, Alireza; Khorashadizadeh, Saeed
SUMMARY: This paper presents a robust adaptive impedance controller for electrically driven robots using polynomials of degree N as a universal approximator. According to the universal approximation theorem, polynomials of degree N can approximate uncertainties including un-modeled dynamics and external disturbances. This fact is completely discussed and proved in this paper. The polynomial coefficients are estimated based on the adaptive law calculated in the stability analysis. A performance evaluation has been carried out to verify satisfactory performance of the controller. Simulation results on a two degree of freedom manipulator have been presented to guarantee its successful implementation.